Total synthesis and stereochemical revision of relgro and 10′-oxorelgro. Issue 22 (23rd May 2019) - Gaddam, Janardhan; Reddy, G. Sudhakar; Marumudi, Kanakaraju; Kunwar, Ajit C.; Yadav, Jhillu S.; Mohapatra, Debendra K.
Abstract : The first total synthesis and correct stereochemical assignments of relgro (6′ S, 10′ S )-configuration and 10′-oxorelgro with (6′ S )-configuration are described. Abstract : The first asymmetric total synthesis and stereochemical assignments of 10-membered macrolactones relgro and 10′-oxorelgro are disclosed. To this end, palladium-catalyzed Stille coupling, the Mitsunobu reaction, ring-closing metathesis, EDCI promoted coupling and the Jacobsen hydrolytic kinetic resolution are used as key steps. The total synthesis followed by thorough evaluation of the optical rotation and CD spectral data led to the revision of the absolute configuration at C-6′ for both relgro and 10′-oxorelgro. Moreover, the 1 H as well as 13 C NMR data are reported for the first time for relgro.